KONTRIBUSI HASIL BELAJAR PENGUJIAN DAN EVALUASI TEKSTIL TERHADAP KESIAPAN MENJADI STAF PENGENDALI MUTU KAIN - Gina Trisnawati; Supandi Supandi (Universitas Pendidikan Indonesia, 2015)
This research examined the contribution of testing and textile evaluation learning result toward the readiness of being a fabric quality controller. This research aimed to disclose how much contribution of testing and textile evaluation learning result toward the readiness of being a fabric quality controller by employing analytical descriptive method. The subjects of this research were 60 students of Textile Technique Department who were chosen randomly in STTT. The data collecting instruments of this present research were the tests and questionnaires. This research disclosed that testing and textile evaluation learning result based on competence to test and evaluate fabric construction, fabric strength, fabric grade, physical characteristics of fabric, and chemical characteristics of fabric were mostly on the high criterion and gave positive contribution significantly toward the readiness of being a fabric quality controller. This research was recommended for students who had not achieved high criterion learning result yet to study harder. This research is also expected to the lecturers of the subject to motivate students to increase their knowledge, manner, and skills in testing and evaluating the textile fabric to gain the optimal learning result.